Contributions to the taxonomy of South African hermit crabs (Crustacea: Decapoda: Paguroidea) – integrating microCT scanning and barcoding - Landschoff, Jannes (Department of Biological Sciences, 2018)
Hermit crabs form an important component of the marine benthos and globally more than 1,200 species have been described. In the unique bioregion of South Africa, hermit crabs are poorly known, and the last taxonomic revision of the group was that of K. H. Barnard in 1950, who recorded only 32 species. This study combines morphological taxonomy, threedimensional (3D) micro-computed tomography (µCT) visualisations, and molecular barcoding to add to, revise, and provide an updated listing of, the regional fauna. The first section of the thesis comprises four chapters, each giving a detailed account of a species either new to science, or to the region. The pagurid hermit crab Goreopagurus poorei, a new species and genus record to the country, is reported and described from deep sea habitats along the Agulhas Shelf, extending the distribution by >10,000 km across the Indian Ocean. Furthermore, three species are described as new to science, one each from the three most common families. The first of these, a deep-water species from a genus of the family Parapaguridae that was previously unknown to South Africa, Paragiopagurus atkinsonae n. sp., is fully described and illustrated, and compared with two other parapagurids that each play a dominant role in the regional benthic offshore invertebrate community. The other two species new to science, Diogenes n. sp. from the family Diogenidae, and Pagurus n. sp. from the family Paguridae, inhabit coastal reefs in subtidal waters off southern KwaZulu-Natal. For the first time in crustacean taxonomy, species descriptions, particularly the one of Pagurus n. sp., are informed by, or based on, µCT imagery of calcified body parts. Following on this technique, Chapter 6 is a short presentation of the 3D raw dataset of seven µCT scans of types and rare museum specimens used in this thesis, which is made publicly available for download. The taxonomic use of the scanning method, with disseminating volumetric data of hermit crabs, is discussed briefly. The final section investigates the fauna as a whole. In Chapter 7, 194 cytochrome c oxidase subunit I gene segments (COI ‘barcodes’) of 43 nominal species plus 12 additional putative species (n = 55 species-like units) were used to validate morphological identifications. Testing this dataset revealed high barcoding efficacy, with nearly 99% identification success rates, and with the best Kimura 2-parameter distance to safely delimit species of hermit crabs of about 3.5%. Chapter 8 updates the regional fauna and provides taxonomic accounts for 62 nominal species which have either been added subsequent to the previous monographic review, or which have undergone taxonomic revision since that time. Of these, 12 are added for the first time here, increasing the number of known South African hermit crab species to 72, an expansion of 56% since Barnard, and about 20% since a recent species list published by W. Emmerson in 2016. Because colour images are provided for 51 out of 72 species, Chapter 8 can also be used as a preliminary guide. However, this study has shown that the hermit crabs of South Africa are by far more diverse than originally thought, and the summary, which includes only the 72 nominal taxa and none of the additional 10 putative species included in the barcoding dataset, is speculated to be only 60–70% complete. Future taxonomic work, especially in the genera Diogenes and Paguristes, will most likely result in many more species descriptions. Therefore, this current study is to be seen as important step towards a fully illustrated taxonomic catalogue on the South African hermit crabs to be produced in the near future.